Contos históricos como instrumento para a educação antirracista: produzindo contranarrativas em sala de aula - NUNES, Marcelo Silva (2024)
In the school environment, diversity is a concept that proposes the inclusion of all students and their differences in the same educational context. In order for this right to be guaranteed, no social group can have its history suppressed from school curricula. Thus, the creation of laws 10.639/2003 and 11.635/2008 became milestones for the process of diversifying the school curriculum, removing from invisibility, traditional peoples and communities (Afro-descendants and indigenous people). Consequently, concepts were reviewed, methodologies were created, and new narratives were produced. But how do these changes occur in educational practice? What kind of training is necessary for teachers? Understanding the stages that make up the elaboration of the school curriculum, the relationship between the school and the community in which the student lives, so that he can perceive his identity, promote mediation between school knowledge and historical knowledge, are some of the themes addressed in this dissertation. For theoretical foundation, we selected authors linked to anti-racist pedagogy: Munanga (2015), Gomes (2015), Castro (2023), among others. Interviews were also conducted with History teachers and visits to schools to monitor the teaching work in the classroom on the theme of education for relations. The objective is to perceive how the dialogue between education and racial discrimination takes place as an aspect to think about the democratization of education, which as a social right must guarantee the right to difference and face the challenge of implementing policies that overcome racial and social inequalities. More than the addition of content, ethnic-racial diversity is synonymous with and a criterion for the quality of the work developed in schools.